Barriers to accepting mental health care in cancer patients with depression. (2nd July 2020) - Niazi, Shehzad; Vargas, Emily; Spaulding, Aaron; Gustetic, Elaine; Ford, Nancy; Paly, David; Tatum, Kelsey; Clark, Matthew M.; Rummans, Teresa
ABSTRACT: This study aimed to determine barriers to accepting mental health care among depressed cancer patients. Cancer patients who screened positive for depression were referred for mental health treatment and sent a validated questionnaire designed to assess barriers to receiving mental health care. Responses were compared between patients who accepted their referral and those who did not. Among 75 patients who agreed to participate, 51 (68%) completed the questionnaire. Reported barriers to accessing mental healthcare were not significantly different between the two groups but patients residing within 50 miles of the clinic had increased odds of attending their appointment.